Spectrum hole identification and exploitation in cognitive radio networks - Vamsi Krishna Tumuluru (2011)
Cognitive radio networks are envisaged as the solution for effective spectrum management for the future communications. In a cognitive radio network, the unlicensed users are permitted to access the unused portions of the licensed spectrum without interfering with the licensed user services. Two mechanisms are instrumental in achieving the above objective, namely, spectrum sensing and dynamic spectrum access. The spectrum sensing mechanism enables the unlicensed users to identify the unused portions of the licensed spectrum (referred as idle channels or spectrum holes) whereas the dynamic spectrum access mechanism facilitates sharing and access of the detected spectrum holes among the unlicensed users. While the spectrum sensing is a physical layer issue, the dynamic spectrum access is a medium access control (MAC) issue. This dissertation aims to address some critical problems related to the design of the cognitive radio networks. Specifically, this dissertation encapsulates the original research contributions made in the course of our research on the cognitive radio networks. The focus of this research is mainly with the MAC layer of the cognitive radio networks.